Walter Benjamin y Hannah Arendt : la noción de tiempo histórico y la tarea del historiador - Goyenechea, Elisa (2011)
Fil: Goyenechea de Benvenuto, Elisa. Pontificia Universidad Católica Argentina; Argentina